DESENTRALISASI DAN KERJASAMA PEMERINTAH - SWASTA - Harsasto, Priyatno (Faculty of Social and Political Sciences Diponegoro University)
Abstract : The vast shifting map of local agencies makes it impossible to treat local government as a single organisation. The externalization of many services, the centralization of others, make local government is only one actor among a network of agencies in a modern-network society. Partnership between local government and private entities is seen as positive, even essential. In Municipality this kind of partnership is the result of a focus on outcomes. Partnership is seen as a vehicle to create mutual trust as well as learning.There have been many progress in innovation of development program, corporate focus, investment in training and leadership development as well as cultural change. However, while progress is being made, the obstacle are still formidable. Key words: Governance, modern-network society, and Public-Private Partnershippermalink : http://ejournal.undip.ac.id/index.php/forum/article/view/3199